Delegated Rulemaking in EU Energy Law : Commission’s Expansive Use of Delegated Acts in Regulation of RFNBOs - Lamri, Lilia (My University, 2025)
This thesis examines the use of delegated acts by the European Commission within the European Union's legislative framework, focusing on the regulation of renewable fuels of non-biological origin (RFNBOs). The thesis aims to determine the legal requirements set for the adoption of delegated acts by the Commission. It then examines whether the Commission has adhered to these legal requirements in the adoption of Article 11, a grandfather clause, of the Delegated Act on the methodology for renewable fuels of non-biological origin (EU/2023/1184). It also explores the broader implications of the extensive use of delegation for democratic accountability within the EU. The research employs a doctrinal methodology, analysing relevant Treaty provisions, legislation such as the Renewable Energy Directive (EU) 2018/2001, and jurisprudence from the Court of Justice of the European Union. A critical legal perspective is adopted to assess potential democratic implications arising from the Commission's use of delegated acts. The findings indicate that while the Commission generally operates within its legal boundaries, specific instances-such as the inclusion of the grandfather clause - suggest potential overreach of delegated powers. The thesis highlights that current mechanisms for legislative oversight may be insufficient and that there exists an imbalance between the European Parliament and the Council, which raises concerns about democratic accountability. The thesis concludes that the broad use of delegation, particularly in rapidly evolving fields like energy and climate law, necessitates enhanced oversight and stricter adherence to legal requirements.

Tämä tutkielma tutkii Euroopan komission delegoitujen asetusten käyttöä Euroopan unionin lainsäädäntökehyksessä keskittyen muuta kuin biologista alkuperää olevien uusiutuvien polttoaineiden (RFNBO) sääntelyyn. Tutkielman tavoitteena on selvittää komission delegoitujen asetusten antamiselle asetettuja oikeudellisia vaatimuksia ja tutkia onko komissio noudattanut näitä vaatimuksia säätäessään komission delegoidun asetuksen EU/2023/1184. Tutkielmassa tutkitaan myös laajempia vaikutuksia, joita laajalla delegoitujen asetusten käytöllä on demokraattiseen vastuuseen Euroopan unionissa. Tutkimuksessa käytetään oikeusdogmaattista tutkimusmetodia, jossa analysoidaan Euroopan unionin perussopimuksia ja asiaankuuluvaa lainsäädäntöä, kuten direktiiviä (EU) 2018/2001 uusiutuvista lähteistä peräisin olevan energian käytön edistämisestä, sekä Euroopan unionin tuomioistuimen oikeuskäytäntöä. Komission delegoitujen asetusten käytöstä johtuvia demokraattisia vaikutuksia tarkastellaan kriittisestä näkökulmasta. Havainnot osoittavat, että vaikka komissio yleensä toimii oikeudellisten rajojensa puitteissa, tietyt tapaukset, kuten RFNBO-sääntely osoittaa, viittaavat toimivallan mahdolliseen ylittämiseen. Tutkielmassa korostetaan, että nykyiset lainsäädännölliset valvontamekanismit saattavat olla riittämättömiä ja että Euroopan parlamentin ja neuvoston välillä on epäsuhtaa valtuutuksen valvomisessa, mikä herättää huolta demokraattisesta vastuusta Euroopan unionissa. Tutkielman johtopäätöksenä on, että laaja valtuuttamisen käyttö, erityisesti nopeasti kehittyvillä aloilla kuten energia- ja ilmasto-oikeudessa, edellyttää tehokkaampia valvontamekanismeja ja tiukempaa oikeudellisten vaatimusten noudattamista.
Keywords: delegated acts, RFNBOs, European Commission, democratic accountability, European Union law, delegoidut asetukset, RFNBO, Euroopan komissio, demokraattinen vastuu, Euroopan unionin oikeus